Impacts of the COVID-19 pandemic on sepsis incidence, etiology and hospitalization costs in France: a retrospective observational study - Marie Al Rahmoun; Alexandre Sabaté-Elabbadi; Didier Guillemot; Christian Brun-Buisson; Laurence Watier (BMC Infectious Diseases)
Abstract Background Sepsis is a serious medical condition that causes long-term morbidity and high mortality, annually affecting millions of people worldwide. The COVID-19 pandemic may have impacted its burden. This study aimed to estimate the impact of the COVID-19 pandemic on sepsis incidence, etiology and associated hospitalization costs in metropolitan France. Methods This retrospective observational study used data drawn from a cohort of hospitalized sepsis patients in France’s national healthcare database. Sepsis was identified through both explicit International Classification of Diseases 10th revision (ICD-10) codes (E-sepsis) and implicit codes (I-sepsis). Participants included all patients aged 15 years or older hospitalized with E-sepsis or I-sepsis in metropolitan France between January 1, 2018, and December 31, 2022. Patient and hospital stay characteristics were described by sepsis type (E-sepsis, I-sepsis) and overall. The distribution of sepsis etiology was estimated for each year. Annual incidence rates were estimated overall and by sepsis type and etiology. Total and median per-stay hospitalization costs were calculated. Results The total age- and sex-standardized sepsis incidence rate per 100,000 increased slightly from 2018 (446, 95% CI 444.2 to 447.7) to 2020 (457, 95% CI 455.1 to 458.6) and then decreased in 2022 (382, 95% CI 380.2 to 383.7) (p <.0001). Incidence rates decreased for both E-sepsis and bacterial sepsis during the pandemic period, whereas I-sepsis incidence increased in 2020 and 2021, associated with a marked increase in viral sepsis and co-infections (p <.0001 for E- and I-sepsis). Viral sepsis represented about 10% of all sepsis cases during the pandemic, but only about 1% prior to the pandemic. Total sepsis-associated hospitalization costs and extra medication costs increased during the pandemic. Characteristics of patients and their hospital stays were overall stable over the five-year study period. Conclusions The COVID-19 pandemic led to a higher burden of sepsis in French hospitals and an increase in hospital stay costs. Critically, our study highlights the need for introducing more explicit viral sepsis codes within the ICD classification system and for achieving a consensus on its definition in order to robustly estimate sepsis incidence.